Search for exotic VZ resonances decaying into a jet and dileptons with CMS - Dias, Flavia A. [UNESP] (My University, 2013)
A search for exotic resonances is performed, with a new particle decaying to a pair of vector bosons VZ, where V is either a W or a Z boson decaying into two overlapping jets and the Z decays to dielectrons or dimuons. The analysis uses a dataset of proton-proton collisions at v s = 7 TeV of center of mass energy, corresponding to 5.0 fb- 1 of integrated luminosity collected by the Compact Muon Solenoid experiment at the Large Hadron Collider in 2011. No significant excess compared to the standard model background expectation is observed in the mass distribution of the VZ candidates. Upper limits at 95% confidence level were set on the production cross section times the branching fraction of hypothetical particles decaying to a pair of vector bosons, as a function of the mass. The limits were interpreted in two benchmark models. Sequential Standard Model W bosons were excluded in the mass range 700 - 929 GeV. Graviton resonances in the Randall-Sundrum model, with k/MPl = 0.05, were excluded in mass range 700 - 924 GeV.